Assessment of the seismic performance of a bituminous faced rockfill dam. Issue 75 (August 2015) - Albano, Matteo; Modoni, Giuseppe; Croce, Paolo; Russo, Giacomo
Abstract: In the attempt to codify a procedure exportable to other similar cases, a thorough investigation of the seismic performance of a bituminous concrete faced rockfill dam built in Italy in the early eighties is herein presented. The dam presents a 90 m tall embankment built in a narrow canyon and is situated in a highly seismic region. The implemented methodology encompasses the indications provided by the most recent literature to point out the problems potentially caused by earthquakes and to account for the paramount factors affecting the response of the dam. Particular attention has been paid to the concept of performance, defining its goals in accordance with the most recent standards and deriving the correspondent limit conditions from observations reported in the literature. In order to optimize the computational effort, dynamic analyses with two and three dimensional finite difference codes have been combined to study the coupled response of the embankment, rocky foundation and bituminous facing. After validating the numerical models with centrifuge tests performed on small scale models of the embankment, the performance of the dam has been investigated with reference to a number of possible scenarios focusing on the amplification spectra, the deformation of the embankment and the integrity of the bituminous lining. Highlights: The seismic performance of a bituminous concrete faced rockfill dam has been investigated. A methodology has been provided according to the most recent literature. Two and three dimensional finite difference models have been developed. The deformation of the embankment has been evaluated according to different scenarios. The integrity of the bituminous facing has been checked.